Impact of pulmonary vein isolation on mechanisms sustaining persistent atrial fibrillation: Predicting the acute response. (1st March 2020) - Dhillon, Gurpreet S.; Schilling, Richard J.; Honarbakhsh, Shohreh; Graham, Adam; Abbass, Hakam; Waddingham, Peter; Sawhney, Vinit; Creta, Antonio; Sporton, Simon; Finlay, Malcolm; Providencia, Rui; Chow, Anthony; et al.
Abstract: Background: Noninvasive mapping identifies potential drivers (PDs) in atrial fibrillation (AF). We analyzed the impact of pulmonary vein isolation (PVI) on PDs and whether baseline PD pattern predicted termination of AF. Methods: Patients with persistent AF less than 2 years underwent electrocardiographic imaging mapping before and after cryoballoon PVI. We recorded the number of PD occurrences, characteristics (rotational wavefronts ≥ 1.5 revolutions or focal activations), and distribution using an 18‐segment atrial model. Results: Of 100 patients recruited, PVI terminated AF in 15 patients; 21.3% ± 9.1% (8.7 ± 4.8) of PDs occurred at the pulmonary veins (PVs) and posterior wall. PVI had no impact on PD occurrences outside the PVs and posterior wall (33.2 ± 12.9 vs 31.6 ± 12.5; P = .164), distribution over the remaining 13 segments (9 [8‐11] vs 9 [8‐10]; P = .634), the proportion of PDs that was rotational (82.9% ± 9.7% vs 83.6% ± 10.1%; P = .496), or temporal stability (2.4 ± 0.4 vs 2.4 ± 0.5 rotations; P = .541). Fewer focal PDs (area under the curve, 0.683; 95% CI, 0.528‐0.839; P = .024) but not rotational PDs ( P = .626) predicted AF termination with PVI. Conclusions: PVI did not have a global impact on PDs outside the PVs and posterior wall. Although fewer focal PDs predicted termination of AF with PVI, the burden of rotational PDs did not. It is accepted though not all PDs are necessarily real or important. Outcome data are needed to confirm whether noninvasive mapping can predict patients likely to respond to PVI.